Empowerment‐Based Positive Youth Development: A New Understanding of Healthy Development for African American Youth. (21st June 2013) - Travis, Raphael; Leech, Tamara G. J.
<x xml:space="preserve">Abstract</x> A shift occurred in research about adolescents in the general population. Research is moving away from deficits toward a resilience paradigm and understanding trajectories of positive youth development. This shift has been less consistent in research and practice with African American youth. A gap also exists in understanding whether individual youth development dimensions generate potential in other dimensions. This study presents an empowerment‐based positive youth development model. It builds upon existing research to present a new vision of healthy development for African American youth that is strengths‐based, developmental, culture‐bound, and action‐oriented. It emphasizes the relationship between person and environment, the reinforcing nature of developmental assets, and the necessity of a sense of community and community engagement for youth.